ORIENTALISME DALAM STUDI ISLAM: SEJARAH, PERKEMBANGAN, DAN TRANSFORMASI KONTEMPORER DI INDONESIA - M. Rivan Febriansyah; Desinta Fitriani Simatupang; Chindi Sri Hariyati; Sulidar Sulidar (ADISAM PUBLISHER, 2026)
Orientalism refers to Western scholarship on the Eastern world, particularly Islam, which from its inception has been closely linked to colonial contexts, religious missions, and political interests. Over time, Orientalism has shifted from an apologetic discourse toward a more systematic academic enterprise through the study of language, philology, and Islamic history. Nevertheless, numerous studies indicate that Orientalism continues to carry epistemological biases that influence how Islam is understood and represented, including within the Indonesian scholarly tradition. This tension between the scholarly contributions of Orientalism and its hegemonic implications constitutes the central concern of this study. This research aims to examine the origins of Orientalism, its historical development, the factors shaping its trajectory, and its contemporary transformation within the context of Islamic scholarship in Indonesia. Employing a qualitative method based on library research, this study analyzes classical Orientalist works, modern academic literature, and critical responses from contemporary Muslim scholars. The analysis is conducted using historical and epistemological approaches to trace shifts in Orientalist paradigms from the colonial period to the post-Orientalist era. The findings reveal that Orientalism is neither a singular nor a static discourse. In Indonesia, its previously dominant influence has gradually declined alongside the growing role of Muslim scholars and the increasing autonomy of Islamic higher education institutions. This transformation has encouraged more dialogical and critical approaches, in which Orientalist methods may be selectively adopted without disregarding Islamic intellectual traditions and perspectives. The study underscores the importance of maintaining a critical and proportional stance toward Orientalism to ensure that the development of Islamic studies remains contextual, balanced, and intellectually equitable